Rates of Burnout Among Collegiate Athletic Trainers During the COVID-19 Pandemic - Lauren Linn; Jennifer Walker; Audrey Wagstaff (Bowling Green State University, 2023)
The purpose of this study was to investigate the effects of COVID-19 related tasks on the rates of burnout in athletic trainers practicing in the collegiate setting.